The Right to Compensation for Moral Damage in Administrative Courts in the Kingdom of Saudi Arabia: A Comparative Study - Balto, Ahmed (Journal of Legal Sciences, 2025)
Compensation for moral damage is in great need of continuous study, in order to adapt to moral effects, and the reason for this is the extreme fatigue as long as the effects of moral effects and then assessing its subject materially, then this depends to a large extent because of its more than objective character, which led to a problem in practical reality, where the inability to compensate for moral damage. The problem is not in the refusal of the judicial authorities to compensate for moral damage, but in the absence of an amendment to estimate compensation for moral damage, and then rule on it.In order to reach a theatrical concept for mechanisms for compensation for moral damage, this study used comparative experiments in addition to analytical description, which helped the researcher to explain, detail and allocate compensation for moral damage in a number of countries, divided into three groups: the first, America and Britain, the second European countries, and the third the Kingdom of Saudi Arabia. The study reached many results, the most prominent of which is: the possibility of proving the right to compensation for moral damage on the control of laws and regulations in these countries, which we divided into three groups. The study recommends the importance of the criteria for determining compensation for moral damage, the more reliance on administrative personal criteria in compensating for moral damage, and the strength of the compensatory bond for this effect, which leads to achieving the goal, which is to reach the appropriate personal recognition in compensation for moral damage.